2007
DOI: 10.1515/dmdi.2007.22.2-3.165
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Diclofenac Sodium After Pretreatment With Diosmin in Healthy Volunteers

Abstract: Diclofenac sodium is a non-steroidal anti-inflammatory drug (NSAID). It undergoes extensive Phase I and Phase II metabolism and in vitro it is a specific CYP2C9 substrate. The first part of the study consisted of oral administration of 100 mg of diclofenac sodium (Voveran100) to 12 healthy male volunteers. Blood samples were collected from the antecubital vein at intervals of 0, 0.5, 1, 2, 3, 4, 5, 6, 7, and 8 hours. The second part of the study was conducted after a washout period of 7 days. Treatment with 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 7 publications
3
17
0
Order By: Relevance
“…10®15¥ For example, Rajnarayana et al showed that oral treatment of healthy volunteers with diosmin increases significantly the bioavailability of metronidazole, 12¥ diclofenac 14¥ and chlorzoxazone, 15¥ and hypothesized that diosmin-induced inhibition of the CYP enzymes catalyzing the biotransformation of these drugs was responsible for the observed pharmacokinetic interactions. We have recently demonstrated that diosmetin, the absorbable aglycone of diosmin, 16¥ to which orally administered diosmin is converted by rhamnosidases of Enterobacteriaceae, 17¥ is a potent in vitro inhibitor of human CYP3A4/5 18¥ and CYP2C9,19¥ the CYP forms responsible for the metabolism of metronidazole and diclofenac, respectively, 12,14¥ thereby confirming the hypothesis of Rajnarayana et al 12,14¥ Since CYP2C9 shares more than 80% amino acid sequence identity with CYP2C8, 20¥ a CYP form expressed at relatively high levels ¤6®7% of total CYP content¥ in human liver 21¥ and which plays a major role in the metabolism of several therapeutically important drugs, 22¥ the main aim of the present study was to assess whether diosmetin is also an effective inhibitor of human CYP2C8. Because in some pharmaceutical preparations the flavone diosmin is associated with the flavanone hesperidin, which is also likely to be hydrolyzed by intestinal microflora to its aglycone hesperetin, 17¥ a further aim of our study was to test the effect of hesperetin on CYP2C8 activity.…”
Section: Introductionsupporting
confidence: 73%
“…10®15¥ For example, Rajnarayana et al showed that oral treatment of healthy volunteers with diosmin increases significantly the bioavailability of metronidazole, 12¥ diclofenac 14¥ and chlorzoxazone, 15¥ and hypothesized that diosmin-induced inhibition of the CYP enzymes catalyzing the biotransformation of these drugs was responsible for the observed pharmacokinetic interactions. We have recently demonstrated that diosmetin, the absorbable aglycone of diosmin, 16¥ to which orally administered diosmin is converted by rhamnosidases of Enterobacteriaceae, 17¥ is a potent in vitro inhibitor of human CYP3A4/5 18¥ and CYP2C9,19¥ the CYP forms responsible for the metabolism of metronidazole and diclofenac, respectively, 12,14¥ thereby confirming the hypothesis of Rajnarayana et al 12,14¥ Since CYP2C9 shares more than 80% amino acid sequence identity with CYP2C8, 20¥ a CYP form expressed at relatively high levels ¤6®7% of total CYP content¥ in human liver 21¥ and which plays a major role in the metabolism of several therapeutically important drugs, 22¥ the main aim of the present study was to assess whether diosmetin is also an effective inhibitor of human CYP2C8. Because in some pharmaceutical preparations the flavone diosmin is associated with the flavanone hesperidin, which is also likely to be hydrolyzed by intestinal microflora to its aglycone hesperetin, 17¥ a further aim of our study was to test the effect of hesperetin on CYP2C8 activity.…”
Section: Introductionsupporting
confidence: 73%
“…We have found that, our results are consistent with a human volunteers study reported by Chow et al (), in which CYP2C9 activity of losartan was decreased after administrating 1 g of RSV per day for 4 weeks. In addition, our results are comparable to a human volunteer study reported by Rajnarayana et al () where an increased C max , AUC and T 1/2 with reduced CL/F were found for DIC after administrating 500 mg of diosmin per day for 9 days and the observed effects are most likely the result of inhibition of activity of CYP2C9 enzyme. In addition, an in vitro study has reported that resvertarol‐3‐sulfate, metabolite of RSV, inhibited the activity of CYP2C9 enzyme (Detampel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the results of a previous pharmacokinetic study (Rajnarayana et al, ), we calculated that 12 healthy volunteers would be required to demonstrate a 20% difference in maximum plasma concentration (C max) and area under the plasma concentration‐time curve (AUC 0‐∞ ) of DIC between control and quercetin treatment phases at a 5% significance level with 80% statistical power. Therefore, 12 healthy male volunteers (age, 26–32; weight, 60–74 kg; and body mass index, 18.30–26.25 kg/m 2 ) were included in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…As a CYP2C9 substrate, DIC has the potential to interact with various inhibitors and inducers of CYP2C9 enzyme. Several drugs (Hynninen et al, ; Kovarik et al, ; Pedrazzoli Júnior et al, ) and herbal constituents (Bedada, Boga, & Kotakonda, ; Bedada, Yellu, & Neerati, ; Rajnarayana et al, ) altered the pharmacokinetics of DIC due to modulation of CYP2C9 enzyme in humans.…”
Section: Introductionmentioning
confidence: 99%